Another breach in the wall: copyright territoriality in Europe and its progressive erosion on the grounds of competition law. Issue 6 (12th September 2016) - Mazziotti, Giuseppe; Simonelli, Felice
Abstract : Purpose: This paper aims to show how the European Commission is seeking to solve the problems of market fragmentation and inaccessibility of copyright content in the Digital Single Market. The analysis draws on a still unresolved conflict between the enforcement of national copyright titles and the European Union (EU) policy objective to ensure pan-European access to copyright works. Design/methodology/approach: First, the paper focuses on the causal relationship between national copyright systems and the existing territorial partitions in the online content markets. Second, the paper reviews the piecemeal approach followed by the Commission in its recent legislative initiative aimed at ensuring the cross-border "portability" of online content services. Third, the paper points out how a much more radical approach the Commission has undertaken in an ongoing antitrust case against the territorial partitions created by major film producers and the biggest EU broadcasters might revisit the principle of copyright's territoriality. Findings: In particular, the paper explains why the application of Article 101 TFEU with regard to the licensing agreements creating areas of absolute territorial exclusivity might have potentially disruptive effects on the existing models of online distribution. While pointing out that this outcome will largely depend on how the ongoing antitrust case will be settled, the paper concludes that the liberalization of so-called "passive sales" might force content owners and broadcasters (or content suppliers) to re-structure markets for online content and to replace territoriality with other criteria that might help them differentiate their offerings and packages. Originality/value: The modernization of copyright rules that the Juncker Commission has advocated since the start of its mandate aims to ensure that consumers can access services, music, movies and sporting events on their electronic devices wherever they are in Europe and regardless of borders. In May 2015, this pledge was transposed in the first pillar of the Commission Communication "A Digital Single Market Strategy for Europe". In particular, the Commission announced its intention to propose, before the end of 2015, legislation to reduce differences and friction between national copyright regimes and prevent "unjustified" geo-blocking. In parallel, DG Competition of the European Commission in its capacity as antitrust authority is conducting a formal antitrust investigation aimed to examine whether territorial licensing agreements concluded by several US film studios with the largest European pay-tv broadcasters could be regarded as incompatible with Article 101 TFEU. For the first time, a paper aims to compare the expected outcome of the ongoing reform of the EU copyright framework vis-à-vis the potential outcome of the antitrust investigation led by DG Competition and identify the pros and cons of the two approaches followed by the Commission.